Secondary Flow Experimental Study for Axial Compressor Cascade Strong Stagger With and Without Tip- Clearance: Static Pressure Distribution on Blade Surface - Syamsuri, Syamsuri (UI Scholars Hub, 2004)
Secondary Flow Experimental Study for Axial Compressor Cascade Strong Stagger With and Without Tip- Clearance: Static Pressure Distribution on Blade Surface. The performance of blade cascade is influenced by the growth and boundary layer’s separation along blade surface and endwall (casing and hub). The secondary flow which happens near hub and casing compressors is three dimentional flow separation phenomenon comes from interaction blade boundary layer with casing and hub boundary layers in the compressor. The secondary flow causes secondary losses, blockage effect, and turning angle (deflection) distribution along blade span. The result of the research shows that the increase of the angle of attack reveals lines of constan pressure to be curved forward (upstream) or pressure gives rise to spanwise caused by a strong curl flow. Separation is also increase and cross between two blades. Hence, three dimentional separation region in corner also increase.